Improving Conventional or Low Dose Metronomic Chemotherapy with Targeted Antiangiogenic Drugs - Kerbel, Robert S. (Korean Cancer Association, 2007)
One of the most significant developments in medical oncology practice has been the approval of various antiangiogenic drugs for the treatment of a number of different malignancies. These drugs include bevacizumab (Avastin®), the anti-VEGF monoclonal antibody. Thus far, bevacizumab appears to induce clinical benefit in patients who have advanced metastatic disease only or primarily when it is combined with conventional chemotherapy. The reasons for the chemo-enhancing effects of bevacizumab are unknown, and this is a subject that we have been actively studying along with additional ways that antiangiogenic drugs may be combined with chemotherapy. In this respect, we have focused much of our effort on metronomic low dose chemotherapy. We have been studying the hypothesis that some chemotherapy drugs at maximum tolerated doses or other cytotoxic- like drugs such as acute "vascular disrupting agents" (VDAs) can cause an acute mobilization of proangiogenic cells from the bone marrow which home to and colonize the treated tumors, thus accelerating their recovery. These cells include endothelial progenitor cells. This systemic process can be largely blocked by a targeted antiangiogenic drug, e.g. anti-VEGFR-2 antibodies. In addition, metronomic chemotherapy, i.e., close regular administration of chemotherapy drugs at low non-toxic doses with no breaks, over prolonged periods of time not only prevents the acute CEP bone marrow response, but can even target the cells. This potential antiangiogenic effect of metronomic chemotherapy can also be boosted by combination with a targeted antiangiogenic agent. Treatment combinations of metronomic chemotherapy and an antiangiogenic drug have moved into phase II clinical trial testing with particularly encouraging results thus far reported in metastatic breast and recurrent ovarian cancer. Oral chemotherapy drugs such as cyclophosphamide (CTX), methotrexate are the main chemotherapeutics used for such trials. Oral 5-FU prodrugs such as UFT would also appear to be highly suitable based on long term adjuvant therapy studies in patients. Recent preclinical results using metronomic cyclophosphamide and metronomic UFT in models of advanced metastatic breast cancer suggest that this type of combination might be particularly promising for metronomic chemotherapy in this indication, particularly when combined with a targeted antiangiogenic drug.